2015
DOI: 10.4103/0973-029x.174641
|View full text |Cite
|
Sign up to set email alerts
|

Honey as an alternative fixative for oral tissue:An evaluation of processed and unprocessed honey

Abstract: Background:Fixation is the most imperative step in the practice of diagnostic histopathology, which is intimately linked to 10% formalin. As a result of increasing concerns about the potential carcinogenicity of the formaldehyde, attempt to find safer alternatives is necessary. Honey has been shown to possess antimicrobial, antiviral and antimutagenic properties. Many studies have reported that honey possesses dehydrating and preserving effects also.Aims and Objectives:To study the fixative properties of proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…[ 6 ] In the presence of water, formaldehyde reacts with hydrochloric acid to form bischloromethyl ether which is a known carcinogen for humans. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 ] In the presence of water, formaldehyde reacts with hydrochloric acid to form bischloromethyl ether which is a known carcinogen for humans. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…also found strong evidence that supports genotoxic and cytotoxic mode of action for the carcinogenesis of inhaled formaldehyde. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…[7,8] Many different studies have already been done to compare honey as fixative in histopatholgy in comparison to formalin, which has provided convincing and appreciable results. [9][10][11] In honey fixed smears one could very clearly appreciate all cellular details such as nuclear, cytoplasmic staining, cellular morphology, clarity and uniformity of the staining which are almost equivalent to ethanol fixed smears. Present study in concordance with Singh A, et al [4] showed that cellularity and cell morphology were well preserved in honey which provides adequate cytological material for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol is classified by the International Agency for Research on Cancer (IARC) as causing cancer in humans following ingestion. 4 Skin exposure from spillages of ethanol can cause burning and stinging. Eye exposure to ethanol can also cause burning and stinging.…”
Section: Fixationmentioning
confidence: 99%
“…Almost all of the slides reported scanty cellularity and were not suitable for diagnosis. Later the sample smeared on to the slide was dried for 1-2minutes and then put into the newer fixative (diluted honey) 4 . These smears were then checked for cellularity, which were adequate for diagnosis or reporting.…”
Section: Loss Of Materialsmentioning
confidence: 99%